Limb ischaemia after intra-arterial injection of Temazepam gel: histology of nine cases. - Dodd, T J (1994)
AIMS--To record the histopathological findings associated with intra-arterial injection of Temazepam gel by nine drug misusers. METHODS--Standard histological examination and immunocytochemistry for endothelial markers (factor VIII related antigen, Ulex europaeus lectin) were carried out. RESULTS--Intra-arterial injection of Temazepam gel may cause severe vascular injury and lead to amputation of fingers or limbs. Histological changes include myocyte necrosis, interstitial oedema, extensive arterial, venous, and capillary thrombosis, and sometimes vasculitis, endothelial swelling, and denudation. CONCLUSIONS--Inadvertent injection of Temazepam gel into arteries may cause catastrophic ischaemic damage, possibly as a result of toxic effects on endothelial cells.